Prevalence of and risk factors for iron deficiency among pregnant women with moderate or severe anaemia in Nigeria: a cross-sectional study - Ochuwa Adiketu Babah; Opeyemi Rebecca Akinajo; Lenka Beňová; Claudia Hanson; Ajibola Ibraheem Abioye; Victoria Olawunmi Adaramoye; Titilope A. Adeyemo; Mobolanle Rasheedat Balogun; Aduragbemi Banke-Thomas; Hadiza S. Galadanci; Nadia A. Sam-Agudu; Bosede Bukola Afolabi; et al. (BMC, 2024)
Abstract Background Anaemia during pregnancy causes adverse outcomes to the woman and the foetus, including anaemic heart failure, prematurity, and intrauterine growth restriction. Iron deficiency anaemia (IDA) is the leading cause of anaemia and oral iron supplementation during pregnancy is widely recommended. However, little focus is directed to dietary intake. This study estimates the contribution of IDA among pregnant women and examines its risk factors (including dietary) in those with moderate or severe IDA in Lagos and Kano states, Nigeria. Methods In this cross-sectional study, 11,582 women were screened for anaemia at 20-32 weeks gestation. The 872 who had moderate or severe anaemia (haemoglobin concentration < 10 g/dL) were included in this study. Iron deficiency was defined as serum ferritin level < 30 ng/mL. We described the sociodemographic and obstetric characteristics of the sample and their self-report of consumption of common food items. We conducted bivariate and multivariable logistic regression analysis to identify risk factors associated with IDA. Results Iron deficiency was observed among 41% (95%CI: 38 - 45) of women with moderate or severe anaemia and the prevalence increased with gestational age. The odds for IDA reduces from aOR: 0.36 (95%CI: 0.13 - 0.98) among pregnant women who consume green leafy vegetables every 2-3 weeks, to 0.26 (95%CI: 0.09 - 0.73) among daily consumers, compared to those who do not eat it. Daily consumption of edible kaolin clay was associated with increased odds of having IDA compared to non-consumption, aOR 9.13 (95%CI: 3.27 - 25.48). Consumption of soybeans three to four times a week was associated with higher odds of IDA compared to non-consumption, aOR: 1.78 (95%CI: 1.12 - 2.82). Conclusion About 4 in 10 women with moderate or severe anaemia during pregnancy had IDA. Our study provides evidence for the protective effect of green leafy vegetables against IDA while self-reported consumption of edible kaolin clay and soybeans appeared to increase the odds of having IDA during pregnancy. Health education on diet during pregnancy needs to be strengthened since this could potentially increase awareness and change behaviours that could reduce IDA among pregnant women with moderate or severe anaemia in Nigeria and other countries.